GES: A validated simple score to predict the risk of HCC in patients with HCV‐GT4‐associated advanced liver fibrosis after oral antivirals. (28th October 2020) - Shiha, Gamal; Waked, Imam; Soliman, Reham; Elbasiony, Mohamed; Gomaa, Asmaa; Mikhail, Nabiel N. H.; Eslam, Mohammed
Abstract: Background & Aims: Hepatocellular carcinoma (HCC) risk persists after hepatitis C virus (HCV) eradication with direct‐acting antivirals (DAAs), particularly in patients with cirrhosis. Identifying those who are likely to develop HCC is a critical unmet medical need. Our aim is to develop a score that offers individualized patient HCC risk prediction. Methods: This two‐centre prospective study included 4400 patients, with cirrhosis and advanced fibrosis who achieved a sustained virologic response (SVR), including 2372 patients (derivation cohort). HCC‐associated factors were identified by multivariable Cox regression analysis to develop a scoring model for prediction of HCC risk; and subsequently internally and externally validated in two independent cohorts of 687 and 1341 patients. Results: In the derivation cohort, the median follow‐up was 23.51 ± 8.21 months, during which 109 patients (4.7%) developed HCC. Age, sex, serum albumin, α fetoprotein and pretreatment fibrosis stage were identified as risk factors for HCC. A simple predictive model (GES) score was constructed. The 2‐year cumulative HCC incidence using Kaplan‐Meier method was 1.2%, 3.3% and 7.1% in the low‐risk, medium‐risk and high‐risk groups respectively. Internal and external validation showed highly significant difference among the three risk groups ( P  < .001) with regard to cumulative HCC risk. GES score has high predictive ability value (Harrell's C statistic 0.801), that remained robustly consistent across two independent validation cohorts (Harrell's C statistic 0.812 and 0.816). Conclusion: GES score is simple with validated good predictive ability for the development of HCC after eradication of HCV and may be useful for HCC risk stratification in those patients.